Biomechanical modeling of musculoskeletal function related to the terrestrial locomotion of Riojasuchus tenuisceps (Archosauria: Ornithosuchidae) - Von Baczko, Belen (2024)
Riojasuchus tenuisceps was a pseudosuchian archosaur from the Late Triassicperiod in Argentina. Like other ornithosuchids, it had unusual morphologysuch as a unique “crocodile-reversed” ankle joint, a lesser trochanter as indinosaurs and a few other archosaurs, robust vertebrae, and somewhat shortened,gracile forelimbs. Such traits have fuelled controversies about its locomotorfunction—were its limbs erect or “semi-erect”? Was it quadrupedal orbipedal, or a mixture thereof? These controversies seem to persist because analyseshave been qualitative (functional morphology) or correlative (morphometrics)rather than explicitly, quantitatively testing mechanistic hypothesesabout locomotor function. Here, we develop a 3D whole-body model ofR. tenuisceps with the musculoskeletal apparatus of the hindlimbs representedin detail using a new muscle reconstruction. We use this model to quantify thebody dimensions and hindlimb muscle leverages of this enigmatic taxon, andto estimate joint ranges of motion and qualitative joint functions. Our modelsupports prior arguments that R. tenuisceps used an erect posture, parasagittalgait and plantigrade pes. However, some of our inferences illuminate therather contradictory nature of evidence from the musculoskeletal system ofR. tenuisceps—different features support (or are ambiguous regarding) quadrupedalismor bipedalism. Deeper analyses of our biomechanical model couldmove toward a consensus regarding ornithosuchid locomotion. Answeringthese questions would not only help understand the palaeobiology and bizarre morphology of this clade, but also more broadly if (or how) locomotor abilitiesplayed a role in the survival versus extinction of various archosaur lineagesduring the end-Triassic mass extinction event.